Química mineral, petrografia, e geoquímica das rochas vulcânicas da Ilha Deception, Antártida - Lima, Rayane Gois de (2017)
The work’s goal is the petrographic, geochemical and mineral chemistry of volcanic rocks from Deception Island, Antarctica. The interpretation of mineral chemistry data of primary minerals from volcanic rocks of pre and post caldera phases, made possible the identifying of chrysolite presence as olivine-type and augite as prevailing clinopyroxene. The plagioclase phenocrystals were classified as bytownite and labradorite. Andesine is the occurrence rare and restricted to the pre-caldera phase. In the matrix, the plagioclase microliths are prevailing labradorite. The chemical characterization of effusive deposits from pre and post caldera were worked through the processing and interpretation from whole rock chemical data. The magmatic process involved in the volcanic rock genesis was a fractionated crystallization of olivine ± clinopyroxene ±plagioclase ±opaque minerals.